Who Leads the Revolutionaries? The Translation Functionalism on the Basis of Some of the Polish Versions of The Twelve by Aleksander Blok - Legeżyńska, Anna (Poznańskie Studia Slawistyczne, 2017)
The article consists of three parts. In the first part, the author interprets the poem of A. Blok as a modernist variant of a “Petersburg Text”, in the second – proposes and explains the formula of the “translation functionalism”, and in the third part, uses it in the analysis of the three Polish translations of The Twelve. The author proves that each of the translators: Wacław Denhoff-Czarnocki, Seweryn Pollak and Wiktor Woroszylski choose a different principle of coherence of the text.This is shown both in the modeling of the city area as well as the social features of the characters. Consequently, three different interpretations of enigmatic epilogue are created, in which the revolutionaries are preceded by Christ carrying a “bloody flag”.